Risk factors for methicillin-resistant Staphylococcus aureus bacteremia: A multicenter matched case-control study (2016)
Introduction: Methicillin-resistant Staphylococcus aureus is a frequent pathogen at critical care services. Its presence leads to increased hospital stays and mortality risk in patients with bacteremia. However, the etiology of this resistance marker has not been fully studied. Objective: To identify risk factors associated with the emergence of methicillin-resistant S. aureus bacteremia in critically ill patients treated at intensive care units in Bogotá, Colombia. Materials and methods: We conducted a retrospective paired case-control study, nested in a cohort of patients diagnosed with S. aureus bacteremia and treated at intensive care units between 2006 and 2008 in Bogotá. Cases were patients with positive blood culture to methicillin resistance, matched in a 1:1 ratio with methicillin-sensitive controls isolated from the same institution and hospitalization year. We used conditional logistic regression to analyze the risk factors associated with the presence of resistance, with emphasis on prior antibiotic therapy. Results: We included 372 patients with S. aureus bacteremia. Factors such as the use of pre-hospital devices: vascular (OR=1.986, 95% CI 1.038 to 3.801) and urinary (OR=2.559, 95% CI: 1.170 to 5.596), along with the number of previously used antibiotics, were associated with the emergence of resistance. The number of antibiotics used previously was determined to have a gradient effect, particularly carbapenems. Conclusions: The rational use of antibiotics and surveillance of exposure to surgical procedures or use of invasive devices are interventions that could diminish the emergence of methicillin-resistant S. aureus bacteremia causes.